The concept of development and rural development Integrated and sustainable (Journal of the College of Basic Education, 2022)
Development is a very broad concept, and in order to get acquainted with all its aspects, one must know what the word development means, what are its most prominent features, and how to achieve development in the presence of obstacles, whether natural or human, or legislation and laws.Agricultural development and integrated rural development are two interrelated concepts. Because they are committed to one principle, which is the elimination of obstacles and problems in the countryside and the need to find remedies for them, whether through laws or legislative procedures, or policies and strategies used to achieve the goals of integrated agricultural and rural development and access to ways to achieve sustainable development in the countryside.